Thermoelectric properties of Yb-filled CoSb3 skutterudites - Park, Kwan-Ho; Seo, Won-Seon; Shin, Dong-Kil; Kim, Il-Ho (Journal of the Korean Physical Society, 2014)
Yb-filled skutterudites Yb z Co 4 Sb 12 (z = 0, 0.1, 0.2, 0.3, 0.4) were prepared by encapsulated melting and hot pressing. The filling effects of Yb on the transport and the thermoelectric properties of the skutterudites were examined. In the case of z ≥ 0.3, a secondary phase (YbSb 2 ) was formed, indicating that the filling fraction limit of Yb was z = 0.2 − 0.3. The intrinsic CoSb 3 had a high positive Seebeck coefficient, but Yb-filled CoSb 3 exhibited a negative Seebeck coefficient. In the case of z ≤ 0.1, the maximum absolute value of the Seebeck coefficient was | −231| μ VK −1 , and in the case of z ≥ 0.2, the absolute value of the Seebeck coefficient increased with increasing temperature. The electrical conductivity increased and the Seebeck coefficient decreased with increasing Yb filling content due to the increased carrier concentration. The thermal conductivity was reduced significantly by Yb filling, mainly due to a decrease in the lattice thermal conductivity. Also, the lattice thermal conductivity decreased with increasing Yb filling content, indicating that the phonon scattering was caused by the rattling of Yb fillers in the voids of the skutterudite structure. Yb 0.2 Co 4 Sb 12 showed the highest figure of merit of 1.0 at 823 K.